Video1_Nitrous oxide dynamics in the Kara Sea, Arctic Ocean.mov - Sofia Muller; François Fripiat; Samuel L. Jaccard; Leandro Ponsoni; Jens A. Hölemann; Alfredo Martínez-García; Bruno Delille (2024)
Previous studies have reported an accumulation of nitrous oxide (N 2 O) on shallow continental shelves of the western Arctic Ocean. In this study, we sampled seawater profiles for N 2 O measurements in the eastern Arctic shelves, in the North Kara Sea, in the context of the Arctic Century Expedition. Despite some variability in the vertical distribution, we typically observe an accumulation of N 2 O in shelf bottom waters, which correlates with a fixed nitrogen (N) deficit. Longer residence times on the shelf promote greater N 2 O enrichment and a larger fixed N deficit. These observations point towards N 2 O production at depth, linked to benthic denitrification processes that are intensified on productive shelve areas. However, in surface waters, physical processes – i.e. temperature-dependent solubility and air-sea exchange – emerge as the main factor controlling N 2 O concentrations. We observe low saturations of 80% at the surface of open ocean stations influenced by water that has previously flowed beneath sea ice. Arctic surface water becomes undersaturated due to cooling and remains undersaturated due to limited air-sea exchange. River supply does not exert a discernable influence on N 2 O concentrations of the studied area. This study reveals the potential of the Arctic Siberian shelves as a sink of atmospheric N 2 O during the summer.